The influence of service quality, tourist attraction and price on tourist satisfaction at Sedulur Dirgantara Park - Riza Afni; Susi Marta Tambunan; Rianto Manurung (Jurnal Mantik, 2023)
Airplanes are a tourist attraction that is popular with all ages. Large objects that can fly are something to behold. Based on this, the manager's idea was formed to create this tourist attraction. This is also interesting for researchers to study because in general tourist attractions sell nature as their attraction, but this looks different because inanimate objects are the attraction. With the help of SPSS 20 and with 100 respondents from visitors supported by statistical analysis with validity tests, reliability tests, classic assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity tests, Multiple Linear Regression tests, Coefficient of Determination tests, partial tests and Simultaneous tests produce a conclusion that partially only attractiveness and price influence consumer satisfaction. However, simultaneously the quality of service, attraction and price influence tourist satisfaction